Sistem Pendukung Keputusan Pemilihan Distro Linux Menggunakan Metode Simple Additive Weighting (SAW) - Renny Puspita Sari; Fiqri Syah Redha (STMIK Budi Darma, 2021)
Linux is a kernel whose development has been very active since it was first released to the public. With a large community, Linux development has penetrated into various fields in the world of computerization, including personal computers. Today, Linux can be used on a variety of devices from personal computers to embedded systems. The development is very active thanks to the large community and Linux adopting open source, many developers are making their own version of the Linux-based operating system. Versions and types of Linux-based operating systems are called distros or distributions. The number of versions and types of Linux-based operating systems, of course, confuses users who are trying Linux for the first time or who want to fully switch to Linux from another operating system. Decision support systems can provide alternative solutions for those users who are confused about choosing a Linux distribution. By using the Simple Additive Weighting (SAW) method, the existing criteria can be used as benchmarks in determining the Linux distribution of choice and therefore the accuracy of the system can exceed 90%